Subjective assessment of the effectiveness of physiotherapeutic methods in lumbosacral discogenic pain syndrome - Michał Grzegorczyk; Piotr Kwiatkowski; Piotr Majcher (Kazimierz Wielki University, 2018)
Aging society, lack of habit shaping attitude to correct posture among children and youth and a lifestyle that often requires excessive effort make lumbosacral discogenic pain syndrome a social disease. It is essential that effective methods for the prevention and treatment of these changes go hand in hand with the frequently occurring pains of the lumbosacral spine. Aim of the study: Comparison of the subjective assessment of the patient's feelings related to the lumbosacral discogenic pain. Material and method: The research group included 60 people diagnosed with a lumbosacral discogenic pain. All patients were divided into three groups of 20 people. Each group was subjected to a different type of rehabilitation, depending on the method analyzed - PNF, manual therapy, and physical treatments. The questionnaire was used as the research tool, it was filled in by the respondents. Results: The patients, before and after the treatments, regardless of the type of rehabilitation to which they were subjected, declared that the most common pain is in the buttock, thigh and calf. Before the rehabilitation, the most frequent additional complaints of the examined patients were numbness and muscle weakness, after rehabilitation it was muscle weakness. After the rehabilitation, the number of painkillers taken by the respondents decreased. Only in the case of patients who underwent physiotherapeutic procedures, the number of people taking medication increased. Conclusions: The best results from the analyzed therapies were obtained after manual therapy. The second most effective was PNF therapy, while the weakest result was achieved by physiotherapeutic procedures.